2022
DOI: 10.1177/10760296221130061
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Neutrophil–Lymphocyte Ratio with Venous Thromboembolism: A Systematic Review and Meta-Analysis

Abstract: The neutrophil–lymphocyte ratio(NLR) has been used for diagnosing venous thromboembolism (VTE). We aimed to assess the accuracy of NLR to diagnose VTE by meta-analysis. Systematic electronic searches were conducted June 2, 2021 in PubMed, Embase(Ovid), and Cochrane Library. The search did not have any language or time restriction applied. Our search strategy was based on keywords in combination with both medical subject headings (MeSH) terms and text words. The diagnostic odds ratio, summary receiver operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Plasma guanosine levels of plasma citrullinated histone H3, a biomarker of NET formation, are associated with VTE in patients with pancreatic cancer (PC). Elevated neutrophil count is a non-specific biomarker of inflammation [ 27 ]. A multicentre retrospective study [ 28 ] showed that postoperative intraperitoneal infection increased the risk of Splanchnic vein thrombosis (SVT).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma guanosine levels of plasma citrullinated histone H3, a biomarker of NET formation, are associated with VTE in patients with pancreatic cancer (PC). Elevated neutrophil count is a non-specific biomarker of inflammation [ 27 ]. A multicentre retrospective study [ 28 ] showed that postoperative intraperitoneal infection increased the risk of Splanchnic vein thrombosis (SVT).…”
Section: Discussionmentioning
confidence: 99%
“…21 In contrast, Rinaldi et al and Hu et al found that a high NLR can be considered a diagnostic marker for VTE. 22,29 Additionally, Farah et al claimed that a high NLR could be a predictor of acute VTE. 30 indicated that a high NLR can increase the risk of VTE.…”
Section: Discussionmentioning
confidence: 99%
“…found that a high NLR can be considered a diagnostic marker for VTE. 22,29 Additionally, Farah et al. claimed that a high NLR could be a predictor of acute VTE.…”
Section: Discussionmentioning
confidence: 99%
“…P-LCR is the percentage of all platelets with a volume greater than 12 fL in the bloodstream and appears to be more sensitive to changes in platelet size than MPV. 5 , 31 This parameter which has not been adequately researched about PE, may guide the diagnosis of PE.…”
Section: Discussionmentioning
confidence: 99%
“…Potential inflammatory biomarkers in the hemogram can guide as useful markers both for explaining the pathogenesis of thrombosis and for diagnosis in PE. 4 6 …”
Section: Introductionmentioning
confidence: 99%